Legal Convergence Related to Investment Policy Problems and Land Acquisition for Industrial Development and National Programs (Journal of Namibian Studies : History Politics Culture, 2023)
The issuance of Law Number. 6 Year 2023 on Job Creation aims to encourage investment, accelerate economic transformation, harmonize central-regional policies, provide ease of doing business, overcome overlapping regulatory issues, and to eliminate sectoral egos. In carrying out investment, the availability of land is the main instrument for national development in Indonesia. However, massive development activities by the government and communities often cause friction in the management, development, security and control of land. Investment policy in its implementation requires land area for industrial development and national programs. This research uses normative-empirical research methods, using a statute approach and social legal approach related to legal convergence related to investment policy problems and land acquisition for industrial development and national programs. The output of this research is first, providing a regulatory map related to legal convergence related to investment policy problems and land acquisition for industrial development and national programs, as well as secondly ideal arrangements related to the sustainability of investment policies and solving land problems.